PERBANDINGAN RESPON SEISMIK BALOK KAYU BIASA DENGAN KOMPOSIT BAJA RINGAN SEBAGAI KOMPONEN STRUKTUR RUMAH TAHAN GEMPA: Penelitian dinamika struktur - Pinondang Simanjuntak (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2021)
abstract Indonesia is one of the areas that are at risk of earthquakes. According to the world earthquake map, Indonesia is located on an area line that is always shaken by earthquakes. The area line is referred to by geologists as "The Pacific Ring of Fire". Therefore, the Indonesian people need a house that has a good dynamic response to the earthquake. In order to understand the dynamic response of earthquake-resistant house structures that are more specific and accurate, a study of the appropriate types of materials to be used as a component of earthquake-resistant housing structures is carried out. Light steel wood to determine the most appropriate type of beam material for earthquake resistant building structures. The dynamic properties studied are related to the reliability of the beam against vibration and repeated deformation as well as the stiffness and strength of the beam structure against dynamic loads. From testing the dynamic response of the selected material, namely the structure of wood beams and lightweight steel composite wood, it was found the right type of material to be recommended as a component of earthquake-resistant residential structural beams. The results of this study serve as a first step to find earthquake resistant housing structures Keywords: dynamic response, deformation, stress. Wooden beam structure, rigidity